Concentration Effect of MgO/K2O Catalyst on Transesterification of Castor Seed (Ricinus communis) Oil: Pengaruh Konsentrasi Katalis MgO/K2O pada Transesterifikasi Minyak Biji Jarak (Ricinus communis) - Santoso, Aman; Sumari, Sumari; Asrori, Muhammad Roy; Ni’mah, Irsyadatun (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Fatty acid methyl esters can be obtained from the synthesis of vegetable oil with methanol using a base catalyst. Vegetable oil has the potential as biodiesel feedstock, the methyl ester character of various vegetable oils is different as from castor seed oil. Synthesis of methyl esters by transesterification reaction with the addition of a heterogeneous catalyst, namely MgO/K2O. The purpose of this study was to synthesize methyl esters from castor seed oil with MgO/K2O catalyst and to determine the yield and character. The research went through 6 stages which included (1) isolation of castor seed oil, (2) determination of free fatty acid (ALB) levels of castor seed oil, (3) manufacture of MgO/K2O catalyst (4) esterification of castor seed oil with H2SO4 catalyst (5) transesterification of jatropha seed oil with methanol and various variations in the concentration of the catalyst MgO/K2O 1%, 2%, 3%, (6) characterization of the synthesized methyl ester which includes tests of density, viscosity, acid number, refractive index and moisture content. The results showed that the concentration of MgO/K2O had an effect on the synthesis of methyl esters from castor seed oil, where the optimization condition was achieved at a concentration of 2% MgO/K2O with a yield of 97.99%. The methyl ester character which is synthesized from castor seed oil with a 2% MgO/K2O catalyst is having a density of 1.0244 g/mL, a viscosity of 22.531 cSt, an acid number of 2.81 g KOH/g methyl ester, a refractive index of 1.456, and a moisture content. 0.035%.